Poly-phenolic fraction of Chrysophyllum cainito extract induces cell death in osteosarcoma cells (Bangladesh Journal of Pharmacology, 2015)
Osteosarcoma shows resistance to chemotherapy and many side effects. The ethyl acetate fraction of ethanolic extract of Chrysophyllum cainito was taken in the present work. The extract was characterized for its phenolic content, antioxidant capacity (ferric reducing antioxidant power and 2,2-diphenyl-1-picrylhydrazyl assays), ability to form reactive oxygen species and annexin V assay. The extract contained phenolic content of 30.1 ± 0.2 mg GAE/g extract. Ferric reducing antioxidant power assay and DPPH assay showed 213.2 ± 12.4 mM Fe2+ equivalent per gram extract and 85.6 ± 4.9 TE/g respectively. For production of reactive oxygen species in the osteosarcoma cells, extract at 50 µg GAE/mLconcentration was statistically equivalent to 100 µM H2O2. EC50 of extract was calculated to be 133 µg GAE/mL in cell viability studies.